2016
DOI: 10.1155/2016/7439605
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Tetanus Immunity in Nigeria: The Effect of HIV Infection on Serum Levels and Transplacental Transfer of Antibodies

Abstract: Background. Tetanus toxoid immunisation of pregnant mother has remained the most effective strategy in eliminating neonatal tetanus. Impaired production and/or transplacental transfer of antibodies may affect the effectiveness of this strategy. We studied the effect of maternal HIV infection on serum levels and transplacental transfer of anti-tetanus antibodies. Methods. A total of 162 mother-baby paired serum samples were taken and analysed for anti-tetanus antibody levels using ELISA. Maternal HIV status was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Actively transported maternal IgG are the source of virtually all the IgG subclasses detected in the fetus and neonates, and these maternally derived levels fall rapidly after birth, reaching a nadir of approximately 4000 mg/dL in term infants at 3–4 months of age ( 66 ). A number of studies have reported reduced levels of maternally derived antibodies to vaccine- or pathogen-specific antigens, including tetanus ( 67 70 ), measles ( 71 , 72 ), Haemophilus influenzae B (Hib), pertussis and pneumococcus ( 69 ), and GBS in HEU as compared to HU newborns (Abu Raya et al in review) ( 73 ). These reduced levels can be related to lower levels of specific antibodies in HIV-infected women, reduced placental transfer, or a combination of these.…”
Section: Part Ii: Immune Alterations Among Heu Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Actively transported maternal IgG are the source of virtually all the IgG subclasses detected in the fetus and neonates, and these maternally derived levels fall rapidly after birth, reaching a nadir of approximately 4000 mg/dL in term infants at 3–4 months of age ( 66 ). A number of studies have reported reduced levels of maternally derived antibodies to vaccine- or pathogen-specific antigens, including tetanus ( 67 70 ), measles ( 71 , 72 ), Haemophilus influenzae B (Hib), pertussis and pneumococcus ( 69 ), and GBS in HEU as compared to HU newborns (Abu Raya et al in review) ( 73 ). These reduced levels can be related to lower levels of specific antibodies in HIV-infected women, reduced placental transfer, or a combination of these.…”
Section: Part Ii: Immune Alterations Among Heu Childrenmentioning
confidence: 99%
“…A Brazilian study found reduced levels of antibodies to tetanus, measles, and pneumococcus in HEU neonates, despite maternal antibody levels that were comparable between HIV-positive and HIV-negative mothers ( 74 ). Bashir et al reported that HIV-positive women were 16.27 times more likely than HIV-negative women to be seronegative for anti-tetanus antibody, while their infants were 33.75 times more likely to be seronegative ( 67 ). They further concluded that HIV-positive mothers were 4.91 times more likely to have poorly efficient transplacental transfer of antibodies.…”
Section: Part Ii: Immune Alterations Among Heu Childrenmentioning
confidence: 99%
“…In UK, maternal HIV infection was associated with a 32% reduction in transfer of TT antibodies, but antibody levels were not significantly different in HEU and HIV-unexposed newborns ( 34 ). Recent data from Nigeria showed that HIV-exposed newborns were nearly 34 times more likely than HIV-unexposed newborns to have seronegative TT titers in cord blood (anti-TT IgG < 0.1 IU/ml) ( 44 ). Although this has not been determined, these data suggest that HEU newborns may be at higher risk of tetanus than children born to HIV-negative women ( 45 ).…”
Section: Impact Of Maternal Hiv Infection On the Transplacental Transmentioning
confidence: 99%
“…36,37 In a study of 162 women published in 2016, eight of ten HIV-infected women remained seronegative (antibody titre <0⋅1 IU/mL) after tetanus vaccination during or before the index pregnancy. 38 HIV infection has also been linked to suboptimal transfer of antipertussis and antitetanus antibodies to infants. 3,37,38,57 In a population with routine tetanus vaccination during pregnancy, HIV-infected women transferred 52% fewer tetanus-specific antibodies to their infants than HIV-uninfected women.…”
Section: Tetanus and Pertussismentioning
confidence: 99%
“…38 HIV infection has also been linked to suboptimal transfer of antipertussis and antitetanus antibodies to infants. 3,37,38,57 In a population with routine tetanus vaccination during pregnancy, HIV-infected women transferred 52% fewer tetanus-specific antibodies to their infants than HIV-uninfected women. 37 Among women who were vaccinated for pertussis or tetanus during pregnancy, HIV-infected women transferred on average 40% less pertussisspecific and 27% less tetanus-specific antibodies to their infants at birth.…”
Section: Tetanus and Pertussismentioning
confidence: 99%